Penyakit kelenjar saliva dan peran sialoendoskopi untuk diagnostik dan terapi - Susyana Tamin; Duhita Yassi (PERHATI-KL, 2011)
Background: Human salivary glands could be prone to diseases. Special tools have been createdto diagnose the disease of the glands and with the advancement of technology, better instruments weredeveloped. Purpose: We present this literature review to share the knowledge of diagnostic and therapyin today’s management of salivary gland disease. Literature Review: Human salivary glands consistedof major and minor salivary glands which produce saliva. Salivary gland secretion is a process that involves cell synthesis and active transport. Salivary gland diseases are also associated with secretion process. Sialoendosopy can be use as diagnostic and therapeutics tool in salivary glands disease. As atherapeutic tool, sialoendoscopy has a role in stone fragmentation and extraction and also dilatation ofstenosis and stricture. Conclusion: Sialoendscopy has many advantages in diagnosis and treatment ofsalivary gland disease, but its employment is still limited because of the high price and required skilledand experienced operator. Key words: salivary gland, salivary gland disease, sialoendoscopy Abstrak : Latar belakang: Kelenjar saliva manusia tidak lepas dari gangguan penyakit. Beberapa alat telahditemukan untuk diagnosis penyakit ini dan dengan semakin berkembangnya teknologi, sangat diharapkanberkembang pula alat diagnosis yang lebih baik. Tujuan: dengan tulisan ini diharapkan dapat memperluaswawasan terhadap perangkat diagnostik dan terapi pada penyakit kelenjar saliva. Tinjauan Pustaka:Kelenjar saliva manusia terdiri dari kelenjar saliva mayor dan minor yang berperan untuk memroduksisaliva. Sekresi kelenjar saliva merupakan suatu proses yang melibatkan sintesis sel dan transpor aktif.Penyakit kelenjar saliva juga berhubungan dengan proses sekresi. Sialoendoskopi dapat digunakansebagai alat diagnostik maupun terapi pada penyakit kelenjar saliva. Sebagai alat terapi, sialoendoskopidapat berperan pada fragmentasi dan ekstraksi batu serta dilatasi stenosis dan striktur. Kesimpulan:Sialoendoskopi memiliki keunggulan dalam diagnosis dan terapi penyakit kelenjar saliva, namunpenggunaannya masih terbatas karena harganya yang mahal dan diperlukan operator yang trampil danberpengalaman. Kata kunci: kelenjar saliva, penyakit kelenjar saliva, sialoendoskopi